Top-down fabrication of single crystal silicon nanowire using optical lithography - Za'bah, Nor Farahidah; Kwa, Kelvin S. K.; Bowen, Leon; Mendis, Budhika; O'Neill, Anthony (American Institute of Physics, 2012)

(untitled)
A method for fabricating single crystal silicon nanowires is presented using top-down optical lithography and anisotropic etching. Wire diameters as small as 10 nm are demonstrated using silicon on insulator substrates. Structural characterization confirms that wires are straight, have a triangular cross section and are without breakages over lengths of tens of microns. Electrical characterization indicates bulk like mobility values, not strongly influenced by surface scattering or quantum confinement. Processing is compatible with conventional silicon technology having much larger critical dimensions. Integrating such nanowires with a mature CMOS technology offers an inexpensive route to their exploitation as sensors.